KOLABORASI PEMERINTAH DAERAH DALAM MENGURANGI ANAK PUTUS SEKOLAH DI KABUPATEN PELALAWAN TAHUN 2017-2018 - Vicky Kusmawati; Rury Febrina (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Department of Education is a government agency that has duties and functions in the field of education. Pelalawan Regency is an area with the number of School Drop Outs Increasing in 2017-2018. So it needs government collaboration with other parties to reduce the number of dropouts in Pelalawan District. This happens because there is still a lack of government socialization to drop out children. The formulation of the problem in this research is How do Actors Collaborate in Reducing School Drop Outs for 2017-2018 and What are the Collaboration Actors in Reducing Dropping Outs for 2017-2018?                The purpose of this study is to find out collaboration actors in reducing school dropouts in 2018-2019 and to describe the collaboration actors in reducing school dropouts in 2017-2018. PThis research is a descriptive study with a qualitative approach. The location of this research was conducted in Pelalawan Regency. Data Collection Techniques are done with Qualitative Data.               The results of the author's research are the Collaboration of Local Governments in Reducing School Drop Outs for 2019-2019. Establishing cooperation between actors in reducing school dropouts so that these programs are implemented well. The collaboration Actor in Reducing School Drop Outs for 2017-2018: Government, Schools, Youth Organization, Parents.